2017
DOI: 10.1371/journal.pone.0171323
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of Karnal bunt pathogen (Tilletia indica) of wheat provides insights into the pathogenic mechanisms of quarantined fungus

Abstract: Karnal bunt disease in wheat is caused by hemibiotrophic fungus, Tilletia indica that has been placed as quarantine pest in more than 70 countries. Despite its economic importance, little knowledge about the molecular components of fungal pathogenesis is known. In this study, first time the genome sequence of T. indica has been deciphered for unraveling the effectors’ functions of molecular pathogenesis of Karnal bunt disease. The T. indica genome was sequenced employing hybrid approach of PacBio Single Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Currently there are six other genomes listed on GenBank for T. indica strains, all originating from India, none with annotations. Two are unpublished and the other four were published too recently to be included in our analyses (Sharma et al 2016, Kumar et al 2017, Kumar et al 2018. There is also a genome for one T. horrida strain originating from China.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there are six other genomes listed on GenBank for T. indica strains, all originating from India, none with annotations. Two are unpublished and the other four were published too recently to be included in our analyses (Sharma et al 2016, Kumar et al 2017, Kumar et al 2018. There is also a genome for one T. horrida strain originating from China.…”
Section: Discussionmentioning
confidence: 99%
“…After manual inspection and verification, only a few candidates with appropriate primer/probe sites were identified and suggested for further wet lab validation in a future study: one for T. controversa, two for T. laevis, one for T. indica, three for T. walkeri and seventeen for T. caries (Table 4). The designed primers and probes were mapped back to all genome assemblies, including those of T. indica (Sharma et al 2016;Kumar et al 2017;Kumar et al 2018) and T. horrida (Wang et al 2015) available on NCBI, and were found to be indeed unique for detecting the intended species for which they were designed (data not shown). To assign putative function to these candidate genes, we analyzed the protein sequence with InterProScan.…”
Section: Candidate Markers For Detection Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Sequenced genome TiK isolate of T. indica was used for identification of candidate pathogenicity/virulence factors homologs using BLASTP search. Identified putative pathogenicity/virulence factors from T. indica genome were subjected to further sequence‐and structure‐based functional annotation.…”
Section: Methodsmentioning
confidence: 99%
“…With this view, the present study was carried out with the aim of comparing the secretomes of T. indica isolates showing differential virulence behavior. Results obtained by comprehensive secretome analysis have been further complemented with the de novo genome sequence generated through the hybrid approach of Illumina HiSeq 2000 and PacBio single molecule real time (SMRT) sequencing . Identified homologs of candidate pathogenicity/virulence factors from T. indica genome were further subjected to sequence‐ and structure‐based functional annotation.…”
Section: Introductionmentioning
confidence: 99%